2013
DOI: 10.5935/abc.20130210
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C, CRP, Log TG/HDLc and Metabolic Syndrome are Associated with Microalbuminuria in Hypertension

Abstract: Background In patients with systemic hypertension, microalbuminuria is a marker of endothelial damage and is associated with an increased risk for cardiovascular disease. Objective To determine the factors that may lead to the occurrence of microalbuminuria in hypertensive patients with serum creatinine lower than 1.5 mg/dL. Methods This cross-sectional study included 133 Brazilians with essential hypertension followed up at a hypertension outpatient clinic. Those with serum creatinine higher than 1.5 mg/dL, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…HUA may directly elevate oxygen partial pressure, leading to proinflammatory response and thus inducing insulin resistance . Meanwhile, serum uric acid and TG/HDL‐C are closely related to each other, whereas high TG and T2DM associated with MAU are independently associated with the risk of macroalbuminuria, and elevation of TG/HDL‐C ratio is independently associated with the progress of MAU . In the present study, after serum uric acid level was effectively controlled by allopurinol therapy, both TG and HOMA‐IR showed an increasing trend compared with data before the treatment.…”
Section: Discussionsupporting
confidence: 44%
“…HUA may directly elevate oxygen partial pressure, leading to proinflammatory response and thus inducing insulin resistance . Meanwhile, serum uric acid and TG/HDL‐C are closely related to each other, whereas high TG and T2DM associated with MAU are independently associated with the risk of macroalbuminuria, and elevation of TG/HDL‐C ratio is independently associated with the progress of MAU . In the present study, after serum uric acid level was effectively controlled by allopurinol therapy, both TG and HOMA‐IR showed an increasing trend compared with data before the treatment.…”
Section: Discussionsupporting
confidence: 44%
“…Hypertension is a major risk factor for cardiovascular disease and one of the most frequent components of metabolic syndrome . Many studies have reported a strong relationship between NAFLD and hypertension .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Hypertension is a major risk factor for cardiovascular disease and one of the most frequent components of metabolic syndrome. 7,8 Many studies have reported a strong relationship between NAFLD and hypertension. 9,10 However, no detailed study has attempted to investigate whether NAFLD is independently correlated with hypertension and blood pressure level.…”
Section: Introductionmentioning
confidence: 99%
“…23 Specifically, a high ratio of triglycerides to HDL-C has an increased prevalence in patients with CKD. [24][25][26] Triglyceride levels commonly are increased in patients with CKD in multivariate analysis whether studied separately 27,28 or combined with Streja et al central obesity as "hypertriglyceridemia waist." 29 In a recent study, 30 both triglyceride and HDL-C levels were associated independently with CKD.…”
Section: Niacin Triglycerides Hdl Cholesterol and Ckdmentioning
confidence: 96%